GREEN SYNTHESIS OF COPPER NANOPARTICLES AND THEIR EFFICACY AGAINST PLANT PATHOGENS (Journal of Plant Disease Sciences, 2017)
Green synthesis of copper nanoparticles (CuNPs) and its use as  antimicrobial activities against plant pathogens is a novel research area. Presently  research was undertaken on synthesis of CuNPs from L. leaves Eucalyptus globules as a reducing agent and copper sulphate as precursor. Synthesized copper  nanoparticles were characterized by Particles Size Analyzer (PSA) and Atomic  Force Microscope (AFM) which showed the size of 30-50 nm. Such confirmed  nanoparticles were evaluated against (Loose smut of wheat) Ustilago nuda tritici  and (Turcicum leaf blight) by spore germination method Exserohilum turcicum which showed 100 per cent spore inhibition over the control at 50 and 100 ppm  respectively. However the synthesized copper nanoparticles were failed to inhibit  the mycelial growth of and by poison Sclerotium rolfsii Macrophomina phaseolina  food technique. Further, CuNPs did not show any phytotoxicity symptoms on  tomato seedlings by spot application on leaves under glasshouse condition.
Keywords: Green synthesis, Copper nanoparticles, Particle Size Analyzer, Atomic Force Microscope, Phytotoxicity and Plant pathogens.